Clot Meniscus Sign Is Associated With Thrombus Permeability and Choice of Mechanical Thrombectomy Technique in Acute Middle Cerebral Artery Occlusion - Nie, Chuang; Kang, Zhiming; Tu, Mengqi; Wu, Xiangbo; Sun, Dong; Mei, Bin (Frontiers in Neurology, 2022)
Background and purpose: The method of mechanical thrombectomy (MT) is related to vascular anatomy and stroke etiology. Meniscus sign and thrombus permeability as imaging markers may be instructive for the selection of MT. This study aims to clarify the relationship between the meniscus sign, thrombus permeability, and the choice of MT in patients with acute middle cerebral artery occlusion. Materials and methods: 111 patients with acute middle cerebral artery occlusion (MCAO) who underwent MT were retrospectively analyzed. Clot meniscus sign was defined as the appearance of meniscoid/edge-like or a single or double-wall contrast channels besides or around insular blood clot. The radiographic, clinical, and surgical data of MCAO patients with or without meniscus sign were compared. Results: The meniscus sign positive group has higher thrombus permeability (HUs) (26.92±9.69 vs. 22.84±7.88, p=0.031) than those without it. Shorter puncture-to-recanalization (P2R) time (65.5 vs. 88.0, p=0.012), higher complete recanalization rate (85.71% vs. 33.33%, p＜0.01), and better clinical outcome (p＜0.01) were obtained by selecting contact aspiration (CA) than stent retriever (SR) in patients with positive meniscus sign. In patients with negative meniscus sign, there was no significant difference in clinical outcome after receiving CA or SR. Conclusions： Patients with MCAO with positive meniscus sign have higher thrombus permeability and are more suitable for CA to acquire better clinical outcomes.